Pragmatic and cultural considerations of compliment responses among Malaysian-Malay speakers - Othman, Normala (International Islamic University Malaysia, 2011)
Janet Holmes defines a compliment as “a speech act which explicitly or implicitly attributes credit to someone other than the speaker, usually the person addressed, for some „good‟ (possession, characteristic, skill, etc.) which is positively valued by the speaker and the hearer” (485). Compliments vary from one culture to another. As suggested by Holmes (1986), compliments are generally paid and appreciated in the Western culture. However, in the Eastern culture, when compliments are paid, they are either rejected or denied (Gu, 1990; Chen, 1993). Malaysia is a multicultural society with a colonial history. English is spoken widely in the country, side by side with several vernacular languages. The study investigates the pragmatics of Malay compliments using Brown and Levinson‟s (1987) “face” framework and Searle‟s (1969) speech act framework among Malay speakers in Malaysia. The results show that compliments when given are more appreciated than denied or rejected by Malay speakers now than before, indicating a shift in the culture of compliments and compliment response in Malaysia. Results also show that compliment responses differ according to the subject of compliment and its relative “distance” to the compliment receiver; closeness causes more compliment rejections, while distance results in compliment acceptance.